Impact of Micronutrient Supplementation on Pesticide Residual, Acetylcholinesterase Activity, and Oxidative Stress Among Farm Children Exposed to Pesticides - Medithi, Srujana; Kasa, Yogeswar Dayal; Kankipati, Vijay Radhakrishna; Kodali, Venkaiah; Jee, Babban; Jonnalagadda, Padmaja R. (Frontiers in Public Health, 2022)
The present interventional study aimed to assess the impact of micronutrient supplementation on pesticide-residues concentrations, vitamins, minerals, acetylcholinesterase activity and oxidative stress among 129 farm children (9–12 years, n = 66 and 13–15 years, n = 63) involved in farming activities in Ranga Reddy district, Telangana, India. Our data showed the presence of five organophosphorus pesticide residues (chlorpyrifos, diazinon, malathion, monocrotophos, and phosalone) among children before-supplementation (both age-groups); while post-supplementation, only two pesticide residues (chlorpyrifos and diazinon) were detected indicating improved metabolic rate. Vitamin E, copper, magnesium and zinc levels were also improved in both the age-groups and manganese levels were significantly increased only among children of 13–15 years age group. Further, post-supplementation also showed an improvement in acetylcholinesterase activity and a decrease in lipid peroxidation among both the age groups of children. However, further research for ascertaining the ameliorating effect of micronutrients in preventing adverse effects of organophosphorus pesticides must be conducted.